The Structural Model of Students' Academic Motivation Based on Teacher- Student Relationship, Attachment to School, and Metacognitive Awareness by the Mediator of Academic Optimism among High-School Students - Atiyeh Amrollahi Beyooki; Mojgan Sepahmansour; Afsaneh Ghanbaipanah (Shiraz University of Medical Sciences, 2020)
Background: It is a widely acknowledged fact that the future lies in the hands of the next generation whose success is mainly dependent on education. The purpose of the present study was to investigate the structural model of students' motivation based on the teacher-student relationship, school attachment, and metacognitive awareness by academic optimism. The method of correlation was structural equation modeling. Methods: The structural equation modeling correlation was the method used in this research. The statistical population of this study consisted of 500 students selected from all male and female high schools in 22 districts of Tehran in the academic year 2017-2018. The Harter Academic Motivation Questionnaire (MIT), Teacher-Student Relationship, Attachment to the Motown School, Mokhtari and Richard Metacognitive Awareness, Academic Optimism were responded. For data analysis, we used Pearson's correlation with SPSS software version 20 and path analysis with Amos software. The level of significance was P>0.01. Results: The results showed that the relationship between teacher-student with academic motivation by mediator role of academic optimism was significant (total effect=0.633, P=0.002), (direct effect=0.286, P=0.002), and (indirect effect=0.377, P=0.002). Furthermore, Attachment to school had a positive association with academic motivation. Finally, the relationship between metacognitive awareness with academic motivation by mediator role of academic optimism was significant (Total effect=0.351, p <0.001). Conclusion: Given the findings of the present study on the importance of the mentioned variables in students' academic motivation, it is suggested that school principals provide positive, active, and vibrant school environment by developing optimistic beliefs in students. Provide students with academic motivation.